2023
DOI: 10.1021/acsomega.2c06776
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Electron Attachment-Induced Radiation Damage to Genetic Materials

Abstract: Reactions of radiation-produced secondary electrons (SEs) with biomacromolecules (e.g., DNA) are considered one of the primary causes of radiation-induced cell death. In this Review, we summarize the latest developments in the modeling of SE attachmentinduced radiation damage. The initial attachment of electrons to genetic materials has traditionally been attributed to the temporary bound or resonance states. Recent studies have, however, indicated an alternative possibility with two steps. First, the dipole-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 220 publications
2
17
0
Order By: Relevance
“…Although the modification of the electrostatic potential that takes into account the induced-dipole by the intramolecular electric field could partially explain the qualitative trend of the experiment, the effect of the quantum-mechanical correlation interaction on the autodetachment dynamics has not yet been fully considered yet. It should be emphasized that the electron-binding nature of DBS is also closely associated with the nonadiabatic transition where the electron in the diffuse nonvalence-orbital is transferred into the valence orbital of the anion, which could lead to the eventual anionic fragmentation reactions. As the DBS plays an important doorway role in such nonadiabatic transitions between the nonvalence- and valence-orbitals of the anion, fundamentally understanding the relation between the nuclear motion and the electron movement (autodetachment and/or electron-transfer) of the DBS is essential for elucidating and/or controlling the whole anionic reaction dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Although the modification of the electrostatic potential that takes into account the induced-dipole by the intramolecular electric field could partially explain the qualitative trend of the experiment, the effect of the quantum-mechanical correlation interaction on the autodetachment dynamics has not yet been fully considered yet. It should be emphasized that the electron-binding nature of DBS is also closely associated with the nonadiabatic transition where the electron in the diffuse nonvalence-orbital is transferred into the valence orbital of the anion, which could lead to the eventual anionic fragmentation reactions. As the DBS plays an important doorway role in such nonadiabatic transitions between the nonvalence- and valence-orbitals of the anion, fundamentally understanding the relation between the nuclear motion and the electron movement (autodetachment and/or electron-transfer) of the DBS is essential for elucidating and/or controlling the whole anionic reaction dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods have addressed the direct and quasi-direct effects of HER and secondary electrons (SEs) on DNA or its constituents. ,, Among these, thin film technology combined with monoenergetic electron beam techniques has allowed adoption of a “bottom up” approach in which one can study DNA damage from electron energies as low as 0.5 eV up to several keVs. As the electron energy is increased, different phenomena gradually step in, and it becomes possible to experimentally distinguish their effects on DNA damage. For example, it has recently been possible to isolate completely from HER-induced chemistry in dry DNA the role of shape resonances [i.e., single-particle transient anions (TAs)] .…”
mentioning
confidence: 99%
“…The interaction of 5 and 10 eV electrons with DNA principally results in the formation of core-excited TAs. , These TAs are formed by temporary LEE capture into the potential well of an electronically excited state of a base. , They can decay by dissociative electron attachment (DEA), thereby leading to BD, or the additional electron transfers to another base or the phosphate group where a lesion can be produced via DEA. When the initial base is left in a neutral dissociative excited state, a double lesion can be formed. , The possible combinations of BDs and transfer sites lead to the damages listed in Table .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that low-energy electrons may induce strand breaks and/or other damage in the biomolecular films of DNA and DNA origami triangles . Solution phase experiments also demonstrated that electrons, while still being quasi-free, may induce bond cleavage in DNA constituents. , In contrast, electrons entering the prehydrated or hydrated stage do not seem to be effective in DEA to DNA nucleobases in solution …”
mentioning
confidence: 99%